Traditions modernisées: Les avis des voyageurs sur le tourisme et les touristes au Maroc - Mihályi, Dorottya (Études sur la Région Méditerranéenne, 2019)
After the independence of the Maghreb states, a special union of tradition and modernity can be observed in relation of travels. This relation can be detected in the simultaneous appearance of the will to return to the traditional values and in the intention to display to the European countries a high level of development which proves the capacity of managing without colonizer forces. These tendencies can be seen in the policies of tourism which is organised by the idea of fascinating the tourist and make it to have a good reputation of the Maghreb countries. Therefore, luxury buildings and places are being constantly constructed, and a European form of entertainment is integrated in the original Arab context. It is also possible to get to know some local traditions, but in a very modernized way, and far from reality. This action of fabricating from the local customs an article of merchandise makes the local people nervous. The relation of tourists and local people are presented from the point of view of an outsider by travellers – who are neither locals nor tourist. They don’t let themselves be influenced by tricks of tourist agencies. They try to avoid touristic places and programs organized to fascinate. The travelogues of independent travellers show us an image of the “fight” between the modern and the traditional in favour of rich European tourists. Travellers draw attention to the lies of touristic system. For this reason, I would like to present travellers’ opinion on modern Maghreb tourism and on sacrificing of old traditions in order to earn more money and show particularly good image of themselves.